Marine systems: Moving into the genomics era - Wilson, K; Thorndyke, M; Nilsen, F; Rogers, A; Martinez, P (2005)
The study of biological systems has been revolutionized by the use of genomic technologies. Most of the knowledge gathered over the last few years refers to terrestrial models. The study of marine systems using genomic technologies has, apart from a focus on microbial systems, been generally neglected although there are signs that this situation may be changing. This review analyses recent progress made in the field of marine genomics and identifies the broad areas in which this new technology is having the greatest impacts. These studies include comparative, functional and environmental genomics of metazoan animals. In many cases, as well as benefiting marine science, studies on marine taxa are having wide-ranging impacts on our global understanding of genomes and genomics. © 2005 Blackwell Publishing Ltd.